CAN EFL LEARNERS' LEARNING STYLES IMPACT THEIR PERFORMANCE ON WRITING SKILL UNDER DIRECT AND INDIRECT CORRECTIVE FEEDBACKS? - Mojtaba Maghsoudi; Sahar Saeedi (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
This study presents the findings of an investigation of the impact of teacher error corrective feedback on 180 field-dependent/ field-independent (FD/FI) male and female pre-intermediate and advanced Iranian EFL learners writing skill. The participants were separated into two experimental groups and one control group and were asked to write three paragraphs of about 100-150 words around three different topics, each in odd days of a week; then they received direct (in experimental group 1), indirect (in experimental group 2) and no correction feedback (in control group). The results based on Mean Scores, Standard Deviation, Multivariate Analyses and 1-way ANOVA showed that there was not any significant difference between the FD/FI learners' writing skill scores who had received corrective feedback on their errors; however, as indicated by the second finding of the present study it would be better to feedback field-dependent/-independent EFL learners indirectly. It was also indicated that, learners' learning styles had made a significant change in their writing skill scores.